SOCIAL ADJUSTMENT AND ACADEMIC ACHIEVEMENT OF EFL STUDENTS AT HIGHER EDUCATION - Sari Anggraeni Sujana; Hariswan Putera Jaya; Fiftinova Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Collegians may find certain difficulties to achieve a good academic achievement. One of the difficulties is their ability on adjusting to their surroundings. Adjusting required the collegians to deal with college environment, academic conditions, and people around them. The purpose of this research was to determine the relationship between social adjustment and academic achievement, as well as the contribution of social adjustment to academic achievement among EFL Students in higher education. The research method used was correlation and the data were analyzed by SPSS 24 with Pearson Product Moment. The sample was a group consisting of 226 active EFL students. The data were collected by testing the instruments which were the revision version of Social Adjustment to College Questionnaire (SACQ) and students' cumulative GPA. The findings revealed a very weak significant correlation between social adjustment and academic achievement, with the r-obtained value greater than the r-table value (0.192 > 0.131) and the p-value less than 0.05 (0.004 0.05) in the significance level of 5% two-tailed. Finally, social Adjustment contributed 3.3 percent to academic achievement.